Implementation of e-commerce as a positive impact by technological innovation - Tasrifan Tasrifan (International Conferences on Educational, Social Sciences and Technology)
A number of technology usage is very high in the last four years around the world, specifically Indonesia. Based on e-marketer survey, since 2014, Indonesia is standing on number six, with number of 88 million people in Indonesia are using Electronic Commerce and continuously increase every year. The purpose of this paper is to know the effect of innovation on technology in purpose of using Electronic Commerce. Electronic Commerce means a transaction of sell and buy product and services through electronic system, such as smartphones, laptops, and netbooks. Internet is the most factor to have online transaction. Electronic Commerce is divided into four types, which are: Business to Business (B2B), Business to Consumer (B2C), Consumer to Consumer (C2C) and Consumer to Business (C2B). In conclude, online transaction make a business become easier and fast.